Addressing Unequal Economic Opportunities : A Case Study of Land Tenure in Ghana - World Bank (Washington, DC, 2012)
The author examine this relationship in the context of agriculture in Ghana's Eastern Region. Our work traces the connection from a set of complex and explicitly negotiable property rights over land to agricultural investment and, in turn, to agricultural productivity. Using survey and focus group data, we find that while the land tenure institutions may have some benefits, they result in drastically lower productivity for those not connected to the political hierarchy. This paper discusses the following topics: land transactions and land rights, land tenure is a political process, and a safety net of sorts.